Basic Training of Arduino Microcontroller Based on Wokwi for Beginner Student Groups - Ahmad Risal; Della Fadhilatunisa; Ninik Rahayu Ashadi; Asmaul Husnah Nasrullah; Anita Candra Dewi (PT. Global Research Collaboration, 2024)
The community service conducted by the team of lecturers from Universitas Negeri Makassar was held at the Electronics Workshop, Department of Educational Electronics, with 15 beginner students registered as participants. The problems identified by the research team, in collaboration with the participants during the socialization, were as follows: (1) The lack of understanding among beginner participants regarding the practice of Arduino-based microcontroller with Wokwi, (2) New students, as beginners, found it difficult to practice with Arduino-based microcontrollers using Wokwi, (3) Beginner participants in the microcontroller practice needed guidance and mentoring from competent individuals to effectively simulate the Arduino-based microcontroller with Wokwi.To address the problems faced by the partners, the solutions offered through this Community Service Program (PKM) were as follows: (1) Providing training to stimulate the potential and interest of the participants, (2) Offering training that integrates knowledge (mathematics, science, and technology) with hardware and software for beginner participants, inviting competent speakers in the field of Arduino-based microcontroller using Wokwi, (3) Conducting training and mentoring to help participants demonstrate Arduino-based microcontroller practice with Wokwi, led by a competent instructor.The method of implementing this activity involved training for beginner students, specifically new students. After being trained, they were mentored to apply the knowledge gained in order to enhance their professionalism in using the Wokwi application. The training was carried out in two main stages: (1) Preparation phase, and (2) Implementation phase of the training. Overall, the results of the Arduino-based microcontroller practice training in the Electronics Workshop of the Educational Electronics Department can be concluded as satisfactory and successful in accordance with the planned objectives. This is reflected in various indicators, including the alignment between planning and implementation, the attendance rate of participants in each session, and the results of the participants' feedback surveys. All the materials planned in the training proposal were successfully delivered as intended. The attendance of the training participants in each session reached 100% of the total 15 registered participants. The activity was also successful in improving the participants' knowledge, skills, and motivation to become more proficient in using the Wokwi application.